Polyhedral metal–organic framework monolayer colloidal crystals with sharpened and crystal facet-dependent selectivity for organic vapor sensing. Issue 16 (13th April 2021) - Yu, Shimo; Wang, Xiang; Jiao, Xiuling; Li, Cheng; Chen, Dairong
Abstract : Polyhedral metal–organic framework monolayer colloidal crystals demonstrate sharpened and crystal facet-dependent selectivity for organic vapors by eliminating grain boundaries and randomly exposed crystal surfaces. Abstract : Metal–organic frameworks (MOFs) are potential sensing materials with inherent sensitivity for molecule detection. However, reliable and reproducible MOF-based optical sensors with well-defined selectivity suitable for practical application have not been reported, which is partly due to the lack of control over film textures, crystalline orientations and exposed crystal facets. Herein, we report on versatile MOF optical sensors based on the self-assembly of polyhedral ZIF-8 crystals into monolayer colloidal crystals (MCCs) with precisely controlled particle sizes, crystalline orientations and specific crystal facets. By eliminating grain boundaries and randomly exposed crystal surfaces, the fabricated polyhedral ZIF-8 MCCs exhibited 'sharpened' selectivity for organic vapors compared with in situ grown ZIF-8 films. The selectivity of polyhedral ZIF-8 MCCs was also found to depend on the exposed crystal facets. Among three polyhedral ZIF-8 MCCs, namely rhombic dodecahedral (RD), truncated rhombic dodecahedral (TRD) and slightly truncated cubic (TC) ZIF-8 MCCs, RD ZIF-8 MCCs exclusively exposing the (110) facets allow the detection of C5–C8 linear alkane, C6–C8 linear alkenes and C1–C8 linear alcohols according to the sequence of the carbon number, while all branched isomers were excluded through size sieving. Combining fast kinetics, wide linear range and excellent reversibility and stability, RD ZIF-8 MCCs were successfully applied for detecting gasoline octane number and achieving colorimetric sensing.